Designing and manufacturing aspherical polystyrene lenses for the terahertz region - Shevchik-Shekera, A.; Zabudsky, V.; Golenkov, A.; Dvoretsky, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
We report on the development of lenses for terahertz vision systems from their design up to manufacturing. Fused deposition modeling was used to assist the 3D printing manufacturing process. HIP (High Impact Polystyrene) used for printing has high transmittance in the terahertz region and low deformation in the manufacturing process. The comparative analysis of experimental parameters data and the designed ones showed good agreement for the aspherical lenses manufactured. Application of the lenses manufactured to get imaging of some objects at 140 GHz radiation with 32 elements linear detector array has been demonstrated.